2008
DOI: 10.1002/jms.1421
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of redox reactions of dyes to variations of conditions created in mass spectrometric experiments

Abstract: Redox behaviour of four imidazophenazine dye derivatives under mass spectrometric conditions of matrix-assisted laser desorption/ionization (MALDI), laser desorption/ionization (LDI) from metal and graphite surface, electrospray, low temperature secondary ion mass spectrometry (LT SIMS) and fast atom bombardment (FAB) was studied and distinctions in the reduction-dependent spectral patterns were analyzed from the point of view of different quantities of protons and electrons available for reduction in differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 47 publications
1
10
0
4
Order By: Relevance
“…58 Soft expansion of the matrix by low-energy secondary electron excitation may be partially blocked by the heat sink. 59 Additional experiments using an electron donor in the Fourier transform ion cyclotron resonance (FTICR) mass spectrometer were conducted that support our conclusion 60 that photoelectrons are also involved in the ionization process. 3,47,61 Therefore, if the MALD process is dominant, and not the heat conduction from the metal to the matrix, then the result may be observed as two contradictory trends.…”
Section: Comparison Of Figs 2a and 2b (And Columns A And A Insupporting
confidence: 55%
“…58 Soft expansion of the matrix by low-energy secondary electron excitation may be partially blocked by the heat sink. 59 Additional experiments using an electron donor in the Fourier transform ion cyclotron resonance (FTICR) mass spectrometer were conducted that support our conclusion 60 that photoelectrons are also involved in the ionization process. 3,47,61 Therefore, if the MALD process is dominant, and not the heat conduction from the metal to the matrix, then the result may be observed as two contradictory trends.…”
Section: Comparison Of Figs 2a and 2b (And Columns A And A Insupporting
confidence: 55%
“…The effect of negative deprotonated molecule formation in LDI MS was recently investigated for the imidazophenazine dyes matrix-free ionization. [22] However, neither [MB − H] −• nor [MB − H] +• ions were detected in DIOS mass spectra of methylene blue recorded from all the studied PS platforms. Hence, the surface species of the PS (Si-H groups, silanol groups and/or adsorbed solvent molecules) act as hydrogen sources for the MB + reduction.…”
Section: Desorption/ionization Mechanismsmentioning
confidence: 97%
“…In-source reductions have also been observed for organic dyes (74,81). Using MALDI, Wada and colleagues (74) analyzed methylene blue, Janus green B, crystal violet, and rhodamine B and found that peaks for [M+1] and [M+2] relative to the [M] peak were significantly increased in comparison to those for theoretical isotopic distribution, demonstrating reduction of (M)H + and (MH)H + .…”
Section: Ecd: Electroncapture Dissociationmentioning
confidence: 98%